The Influence of Workload and Work Stress Mediated by Burnout on Cyberloafing Behavior in the Pharmaceutical Industry's R&D Department - Juniar, Robbi; Arijanto, Agus (Indonesian Journal Publisher, 2024)
This study aims to determine how burnout-mediated cyberloafing behavior influences employee performance, focusing on workload and work stress. The research population consists of 165 employees from Pharmaceutical Industry R&D Department, with the same number forming the sample based on saturated sampling. The sampling method employed is convenience sampling. Data collection involves using a questionnaire as the survey instrument. Data analysis utilizes Partial Least Squares. The study reveals a robust correlation between workload and cyberloafing behavior. Job stress significantly influences cyberloafing behavior, while workload significantly impacts burnout. Burnout, in turn, significantly affects cyberloafing behavior. Workload affects cyberloafing behavior both directly and indirectly through burnout as a mediating factor. Workplace stress functions as a mediator between cyberloafing and burnout.